(untitled) (2016)
There is not a current method to estimate South American freshwater stingray’s abundance. Therefore we designed a census method and tested it in the field. It consists of making nocturnal surveys by boat in large rivers (>25m width) and floodplain lagoons of varying sizes, along transects of 100m x 10m (1000 m2). We applied this method in the Tomo River, a tributary of the Orinoco River in Colombia. 110 transects were surveyed in 200 runs. A total of 149 rays of four species were recorded: Potamotrygon motoro, Potamotrygon orbignyi, Potamotrygon schroederi and Paratrygon aiereba. P. motoro was the most abundant with a density of 0.31 individuals /1000 m2 (SD=0.5). This method gave optimal results when applied to habitats with high transparency and shallow depth (< 1m) since it permitted the identification of both adults and juveniles present.